THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON COMPANY PROFITABILITY AND REPUTATION: EVIDENCE OF LISTED FIRMS IN INDONESIA - Gara, Reply (ACCOUNTABILITY, 2020)
Corporate social responsibility or later abbreviated to CSR has become a trend and a hot topic that is widely discussed in Indonesia. Business practices in the past that tended to have a negative impact, made the discourse on corporate social responsibility or CSR. There seems to be a paradigm shift from being initially profit oriented, where any activity must be viewed from the point of adding financial benefits or not, becoming more concernedtowards socially responsible responsibilities. This topic became even more interesting with the enactment of Law no. 40 of 2007 concerning Limited Liability Companies, (UUPT) as of August 16, 2007, has given rise to a variety of controversies and disagreements. The resultsshow thatcorporate social responsibility disclosure is significant on profitability (ROA) ofhigh profile, but not significant on low profile firms. The Corporate Social Responsibility disclosure is significant on profitability (ROE) of high profile and low profile firms. The Corporate Social Responsibility disclosure is significant on reputation of high profile and low profile firms.